Perception et gestion de l’érosion et des ressources en eau par les agriculteurs et les éleveurs du bassin versant de l’ibicuí (RS, Brésil) - Guillaume Leturcq; François Laurent; Rosa Vieira Medeiros (Confins)
Perception and management of the erosion and the waters resources by the farmers in the Ibicuí basin (RS, Brazil). The west of the Rio Grande do Sul is dominated by the culture of soya, rice and by the bovine breeding. In the sandy part, the environment is affected by erosion producing of spectacular forms (arenização) remaining in imaginary those of the deserts. The agricultural production is important and generates large uptakes of water for the irrigation of rice but also the use of pesticides for the whole of the cultures. Sustainable management of the water and soil resources of this area requires actions of conservation. Then, several questions emerge: how the farmers perceive these phenomena? Do they constitute for them stakes? How do their reason agricultural practices? In which social networks? Which are the interactions with the government?Adopted methodology is based on interviews with 23 farmers. The aim is to better understand their perception and management of the environment and to identify the social variables of the differences in behaviour.The results show that few farmers perceive their responsibilities in the soil erosion and the problems of water resources. So risks of lack of water are perceived by some of them, they are reduced primarily to the dryness and the overexploitation of the resources is not considered. Water pollution is neglected. The erosion in the areas of “arenização” is not regarded as a stake: these areas are unproductive but do not threaten the total productivity of the farms. It is more a “banal” erosion of the cultivated pieces which worries the farmers and which led a great part of them to move to no-till. The knowledge of the local environmental stakes as the actions of conservation is not transmitted by the government. This research shows us finally that a better environmental risk management will go through a comprehensive approach of the technical and cultural universe of the farmers like their economic constraints.